The Kedudukan Hukum Surat Kuasa Membebankan Hak Tanggungan yang dibuat PPAT: Kedudukan Hukum Surat Kuasa - SULISTYAWATI, NI PUTU YUNIKA (VYAVAHARA DUTA, 2025)
Abstract An agreement is an event where one person promises to another person or where two people promise each other to carry out something. From this event, a relationship arises between the two people which is called an alliance. Thus, the relationship between an agreement and an agreement is that the agreement issues an obligation. Agreements are a source of engagement, in addition to other sources. This means that an agreement is an abstract meaning, while an agreement is a concrete thing or an event. The method used is a normative method, there are 2 benefits of this research, namely theoretical benefits and practical benefits. The theoretical benefits of this research are expected to contribute to increasing information and insight in discussing the problem of land ownership fraud. And the practical benefit of this research is that through this research it is hoped that it will provide an overview, input and suggestions for the general public, the position of a power of attorney that imposes mortgage rights made by PPAT Requirements and documents needed in the process of making a deed. The following are the conditions for making a SKMHT. It does not contain the power to provide other legal action, but only relates to the imposition of mortgage rights. debtor. The function of the Power of Attorney to Install Mortgage Rights (SKMHT) in Granting Mortgage Rights in the Perspective of Law Number 4 of 1996 concerning Mortgage Rights. The legal position of the Power of Attorney deed to encumber the mortgage rights made by PPAT is that it is an additional/additional agreement (accessoir) which gives rise to a legal relationship between debts and receivables (credit agreement). Because Mortgage Rights are by their nature a subsidiary agreement or accessoir to certain receivables, which are based on a principal agreement, their birth and existence is determined by the existence of receivables whose repayment is guaranteed. The form of SKMHT is regulated in the provisions of Article 15 UUHT.